Chapter Forme e figure della psicomotricità - Padoan, Ivana Maria (Studi e saggi, 2019)
Psychomotor education became an educational practice around the 1960s. Its history, research and practices are affected by the educational transformation of a transmission or application model of intervention towards a global and relational educational process of the person through discovery, research and active practices. Starting from these references, psychomotor education is based on a personal epistemology of knowing and learning by the subject as a global, autopoietic, dynamic system, embodied in the context of action. However, the educational dimension of psychomotricity is not limited to the educational process alone. If its origin mostly presents a re-educational matrix, development has taken on a path of prevention, support and educational, re-educational and therapeutic support. Its cultural and theoretical references are complex and interdisciplinary and emphasize the domination of the autopoietic and self-referring subject of its future.